The Cortical Physiology of Ipsilateral Limb Movements. Issue 11 (November 2019) - Bundy, David T.; Leuthardt, Eric C.
Abstract : Whereas voluntary movements have long been understood to derive primarily from the cortical hemisphere contralateral to a moving limb, substantial cortical activations also occur in the same-sided, or ipsilateral, cortical hemisphere. These ipsilateral motor activations have recently been shown to be useful to decode specific movement features. Furthermore, in contrast to the classical understanding that unilateral limb movements are solely driven by the contralateral hemisphere, it appears that the ipsilateral hemisphere plays an active and specific role in the planning and execution of voluntary movements. Here we review the movement-related activations observed in the ipsilateral cortical hemisphere, interpret this evidence in light of the potential roles of the ipsilateral hemisphere in the planning and execution of movements, and describe the implications for clinical populations. Highlights: Unilateral limb movements are generally understood to be driven by the cortical hemisphere opposite to the moving limb, but there is increasing evidence that the hemisphere on the same side as the limb is also active during movements. These same-sided motor activations are robustly observed across numerous recording modalities and species and complex movement information can be decoded from the neural population activity. Ipsilateral motor activity has been proposed to represent a number of functions, including interhemispheric inhibition, maintaining an efferent copy of the state of the ipsilateral limb, and contributing to the planning and execution of voluntary movements. Growing evidence supports a complex role of the ipsilateral hemisphere in motor control, with the specific contributions varying according to task demands and timing.